CLINICAL-IMMUNOLOGICAL ASSESSMENT OF EFFICACY OF NEOADJUVANT PHOTODYNAMIC THERAPY IN SURGICAL MANAGEMENT OF PRIMARY MELANOMA - G. I. Gafton; V. V. Anisimov; M. L. Gelfond; Yu. V. Semiletova; I. A. Baldueva; Т. L. Nekhaeva; A. V. Novik; М. Yu. Myasnyankin (Сибирский онкологический журнал)
Efficacy of neoadjuvant photodynamic therapy (PDT) with photoditazine and radachlorine was assessed in 42 patients with stage I–III primary melanoma. The control group consisted of 42 patients with melanoma who underwent surgery alone. The 2.5-year overall and recurrence-free survival rates were significantly higher in patients who received neoadjuvant PDT than in the control group patients.  Neoadjuvant PDT performed 2 days before surgery was found to promote the activation of T-and B-cell immunity.   In the experimental study it was shown that the increase in time of laser irradiation of melanoma cell culture accompanied by a significant increase in the proportion of late apoptotic cells.